Transformasi Digital dalam Manajemen Pendidikan Nonformal di Taman Pendidikan Al-Qur’an (TPQ) Al Manar - Rahmah, Ica Suci; Mubarak, Luthfi Adli (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Digital transformation in non-formal education management is a change in management through the use of technology. However, non-formal education has challenges in adapting technology due to limitations that give rise to the digital divide, low competence and limited resources. This study uses a descriptive qualitative approach by reviewing various sources of literature, national policies, and case studies in the field. The aim is to find out how digitalization can affect non-formal education. This study shows that digital transformation has a significant impact on increasing managerial efficiency, affordability of education services, and quality of learning. Innovation in technology applied to educators and students is expected to be a means of facilitating the learning process. Thus, digitalization is not only a technical aid, but also a transformational strategy in strengthening the role of non-formal education as a means of education for the community.